2008
DOI: 10.1053/j.gastro.2008.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Progenitors of Interstitial Cells of Cajal in the Postnatal Murine Stomach

Abstract: Background & Aims-Maintaining the integrity of networks of interstitial cells of Cajal (ICC) is essential to preserve orderly contractile activity and neuroregulation in the gastrointestinal tract and to restore these functions after tissue damage or surgeries. Maintenance of ICC requires insulin-or insulin-like growth factor-I (IGF-I)-dependent production of membrane-bound stem cell factor (SCF) and may involve regeneration from local progenitors. Our goal was to identify ICC precursors in postnatal murine ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
204
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(212 citation statements)
references
References 37 publications
8
204
0
Order By: Relevance
“…It has previously been proposed that CD34‐positive fibroblast‐like ICCs cells were progenitors of c‐kit‐positive ICCs in the intestine 43, 44. Our data point to the presence of CD34‐positive cells surrounding prostatic budding on the early prostate development, later CD34/c‐kit‐positive cells and c‐kit‐positive cells are verified in this region, while CD34‐positive cells form a network of telopodes in the interalveolar region.…”
Section: Discussionsupporting
confidence: 66%
“…It has previously been proposed that CD34‐positive fibroblast‐like ICCs cells were progenitors of c‐kit‐positive ICCs in the intestine 43, 44. Our data point to the presence of CD34‐positive cells surrounding prostatic budding on the early prostate development, later CD34/c‐kit‐positive cells and c‐kit‐positive cells are verified in this region, while CD34‐positive cells form a network of telopodes in the interalveolar region.…”
Section: Discussionsupporting
confidence: 66%
“…In healthy, ICC numbers are dynamic (39) indicating that the integrity of the ICC networks has to be tightly controlled with processes that regulate both ICC loss and ICC replacement. ICC loss might be due to apoptosis (39) and trans/ de-differentiation (40,41) whereas ICC replacement includes cell repair, proliferation from adult ICC and ICC stem cell precursors proliferation (42). As reported above, the c-Kit signaling pathway is responsible for ICC development and maintenance of the phenotype.…”
Section: Icc and Nerve Contactsmentioning
confidence: 93%
“…Therefore, the possibility that local ICC precursors are present in the gut wall has taken hold. Studies in postnatal murine gastric muscle revealed rare cells that expressed very low level of c-Kit and normal level of CD44, CD34, Ano-1, and receptors for insulin and IGF-1 (42,43). In adult mouse colon, 14 days after BAC treatment, the damaged areas re-innervated and together with the nerve structures, cells with FLC features were detected.…”
Section: Icc and Nerve Contactsmentioning
confidence: 99%
“…No other major cell type in the small intestine appears to express CD44 (Chen et al 2007). Lorincz et al (2008) found that mature ICC are Kit …”
mentioning
confidence: 99%